Lectotype designations for Ptychoderini species (Coleoptera, Anthribidae, Anthribinae) of the Muséum National d'Histoire Naturelle - Mermudes,Jose Ricardo M. (2010)
Based on a study of the type material housed in the Muséum National d'Histoire Naturelle Paris, lectotypes are designated for the following species: 1) described by Jekel in 1855 - Ptychoderes columbianus, P. callosus, P. mixtus, P. antiquus, Hypselotropis batesi, Ectatotropis conicollis, and Tropipygus speciosus; 2) described by Thomson in 1858 - Phloeotragus sparsutus. The following species have the type specimens illustrated: Ptychoderes mixtus, lectotype female; P. tricostifrons, holotype male; Hypselotropis speciosa, lectotype male; Phloeotragus sparsutus, lectotype male and paralectotype female.